Indonesian Agricultural Industry Innovation to Create World Food Storage in 2045 - Dandi, Muh Zulhamdi Suhafid; Musabbihah, Mulkis (MultiTech Publisher, 2024)
The issue of food safety and food security has become an international concern, given the increasing global food demand due to the food crisis caused by the Covid 19 pandemic. Indonesia is trying to become a global food supplier through the Indonesian government's vision of